(untitled) (Jurnal Bahasa Lingua Scientia, 2024)
The objectives of this research were to investigate the use paraphrasing technique and their paraphrasing preference by ELE seniors of Universitas Negeri Malang. The research used quantitative method and used questionnaires as the instrument to collect the dat. The questionnaires of this study were distributed to 61 students who writing their thesis since they required to do paraphrasing a lot to write their thesis. Finally, the results of the study show the most paraphrasing technique used by the students in syntactic paraphrasing is changing active sentence into passive sentence, while in semantic paraphrasing the most paraphrasing technique used by the student is changing word order by changing its synonym. Moreover, the result of this research shows that the students prefer using paraphrasing tools since its practicality to be used by the students to help them paraphrase from original sources.